Construction of lanthanide complexes based on 3, 4-dichlorobenzoic acid and 5, 5′-dimethyl-2, 2′-bipyridine: Supramolecular structures, thermodynamic properties and luminescent behaviors. (1st September 2019) - Meng-Xue, Zhou; Ning, Ren; Jin-Yong, Hu; Jian-Jun, Zhang; Da-Qi, Wang
Graphical abstract: Binuclear complexes1 –2 are isomorphous and crystallize in the triclinic crystal system and P 1 ¯ space group, and each metal center is eight-coordinated with distorted square antiprismatic molecular geometry. Complexes1 –2 are stitched together via π–π stacking interactions and hydrogen bonding interactions to form the 1D, 2D supramolecular structures. The thermal decomposition mechanisms of two complexes were obtained by TG-DSC/FTIR techniques. The molar heat capacities of the complexes1 and2 are measured by a DSC instrument over the temperature range from 255.15 to 323.15 K and thermodynamic functions were calculated by fitted polynomial and thermodynamic equations. The photoluminescence studies demonstrate that complex2 exhibits the characteristic emission of Tb 3+ ion ( 5 D4 → 7 F6-3 ). Abstract: Two novel lanthanide complexes, [Ln2 (3, 4-DClBA)6 (5, 5′-DM-2, 2′-bipy)2 (C2 H5 OH)(H2 O)] (Ln = Gd(1 ), Tb(2 )); 3, 4-DClBA: 3, 4-dichlorobenzoate; 5, 5′-DM-2, 2′-bipy: 5, 5′-dimethyl-2, 2′-bipyridine) have been hydrothermally synthesized and structurally characterized by elemental analysis, IR spectrum, thermal analysis and single X-ray diffraction techniques. The binuclear complexes1 –2 are isomorphous and crystallize in the triclinic crystal system and P 1 ¯ space group, and each metal center is eight-coordinated with distorted square antiprismatic molecular geometry. The structure of this type of complex is unique in that the solvent ethanol molecule participates in the coordination. Complexes1 –2 are stitched together via π–π stacking interactions and hydrogen bonding interactions to form the 1D, 2D supramolecular structures. The thermal decomposition mechanisms of two complexes were obtained by TG-DSC/FTIR techniques. The molar heat capacities of the complexes1 and2 are measured by a DSC instrument over the temperature range from 255.15 to 323.15 K and thermodynamic functions were calculated by fitted polynomial and thermodynamic equations. The luminescence studies demonstrate that complex2 exhibits the characteristic emission of Tb 3+ ion ( 5 D4 → 7 F6-3 ).